Effect of obesity and blood pressure dipping status on left ventricular mass in normotensive young adults - Nur Fitriani; Syakib Bakri Bakri; Hasyim Kasim; Haerani Rasyid; Sitti Rabiul Zatalia; Nasrum Machmud; Ahkyar Albaar; Andi Makbul Aman; Pendrik Tendean; Faridin Pango; Ilham Jaya Pattelongi (Український Журнал Нефрології та Діалізу, 2024)
Despite the established links between obesity, blood pressure variability, and cardiovascular risks, the specific impact of the interaction between obesity and non-dipping blood pressure status on left ventricular mass (LVM) in normotensive individuals remains underexplored. Most studies have focused on hypertensive populations, leaving a critical gap in understanding how these factors contribute to cardiovascular changes in normotensive young adults. This study aims to address this gap by examining the combined effects of obesity and blood pressure dipping status on LVM in a normotensive cohort of young subjects.